Social sciences: the big issues - Woodward, Kath (Routledge, 2014)
"Social Sciences: The Big Issues third edition offers an introduction to the big debates within the social sciences and to what the social sciences can provide as a means of explaining the changing world. The social sciences focus upon people as individuals and as members of wider communities and networks, and look at all aspects of human relationships from the personal and intimate to the public and political. The book covers contemporary concerns with identities, citizenship, migration, diversity, new technologies, and the changing and often uncertain impact of globalization. The third edition has been extensively updated with new illustrations and examples, and additional discussion of the responses of the social sciences to the mobilities of contemporary life, such as migration, living in multiethnic and often rapidly changing communities, new forms of citizenship, the impact of the material world, the perception that we live in a more insecure and dangerous world and the role of the media in presenting ideas about the changes that might be taking place"--